Potential of Spirulina platensis as a feed supplement for poultry to enhance growth performance and immune modulation - El-Shall, Nahed A.; Jiang, Shouqun; Farag, Mayada R.; Azzam, Mahmoud; Al-Abdullatif, Abdulaziz A.; Alhotan, Rashed; Dhama, Kuldeep; Hassan, Faiz-ul; Alagawany, Mahmoud (Frontiers in Immunology, 2023)
Due to the rise in drug-resistant strains of bacteria as well as ineffective immunization efforts to combat pathogenic viruses, bacterial and viral illnesses pose a significant direct danger to the poultry industry. One of the most widely used dietary supplements, is spirulina, which is becoming more popular for usage as a nutritional and therapeutic approach in the human, animals, poultry and aquaculture industries. It has high quantities of protein, vitamins, minerals, vital fatty acids, pigments, and essential amino acids. Chickens' gut microbial population, serum biochemical parameters, hematology, and growth performance might all be improved by inclusion of Spirulina. Polyphenols, carotenoids, and phycocyanin are a few of the unique natural antioxidants found in it. Additionally, it contains a lot of total phenols, which has antibacterial benefits. Spirulina extracts inhibit bacterial motility, invasion, biofilm formation, and quorum sensing in addition to acting directly on the bacterium by weakening and making the bacterial cell walls more porous, which results in cytoplasmic content leakage. Additionally, Spirulina exerts an antiviral activity against certain common human or animal viruses so an emphasis on potential benefits against avian viruses was taken into consideration. Spirulina, a calcium-rich internal polysaccharide of Spirulina, may be responsible for this antiviral impact through inhibiting the entry of several viruses into the host cells, boosting the creation of nitric oxide in macrophages, and stimulating the generation of cytokines. More focus has also been placed on the immuno-stimulant effects of it on poultry's immune system, which has boosted disease resistance and improved survival and growth rates, particularly during exposure to stress factors. Consequently, its potential medicinal uses as an antibacterial, antifungal, and antiviral agent were reviewed here, along with its immune-stimulating properties and its utilization to compensate some of the managerial inadequacies in chicken farms.